2019
DOI: 10.1038/s41438-019-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene regulatory pathways and co-expression networks associated with fire blight infection in apple (Malus × domestica)

Abstract: Apple cultivars with durable resistance are needed for sustainable management of fire blight, the most destructive bacterial disease of apples. Although studies have identified genetic resistance to fire blight in both wild species and cultivated apples, more research is needed to understand the molecular mechanisms underlying host-pathogen interaction and differential genotypic responses to fire blight infection. We have analyzed phenotypic and transcriptional responses of 'Empire' and 'Gala' apple cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 61 publications
0
25
1
Order By: Relevance
“…Young plants were inoculated with different E. amylovora strains, once shoot length of the majority (90%) of the plants was above 15 cm. Inoculum was prepared with a concentration of 10 9 as described earlier (Silva et al 2019 ; Khan et al 2006 ). Scissors were dipped in the inoculum and used to cut the youngest leaf (1–2 cm size) for inoculation at approximately the start of the broadest part of the leaf.…”
Section: Methodsmentioning
confidence: 99%
“…Young plants were inoculated with different E. amylovora strains, once shoot length of the majority (90%) of the plants was above 15 cm. Inoculum was prepared with a concentration of 10 9 as described earlier (Silva et al 2019 ; Khan et al 2006 ). Scissors were dipped in the inoculum and used to cut the youngest leaf (1–2 cm size) for inoculation at approximately the start of the broadest part of the leaf.…”
Section: Methodsmentioning
confidence: 99%
“…Upon analysis of RACs of non-grafted 'M.7' rootstocks on fire blight susceptibility of above-ground leaf tissues, it is observed that increased root surface area contributed to decreased fire blight susceptibility in these above-ground leaf tissues, and the reverse is found to be true as well. These observed root-dependent differences in levels of fire blight disease susceptibility may be attributed to presence of multiple defense mechanisms [11,25,38,39,40] that interact with the pathways related to nutrient status of a plant. Indeed, involvement of diverse molecular pathways related to plant metabolism, cell cycle, oxidation-reduction, and stress response suggests presence of systemic regulation of fire blight infection in apples [11,38].…”
Section: Discussionmentioning
confidence: 99%
“…These observed root-dependent differences in levels of fire blight disease susceptibility may be attributed to presence of multiple defense mechanisms [11,25,38,39,40] that interact with the pathways related to nutrient status of a plant. Indeed, involvement of diverse molecular pathways related to plant metabolism, cell cycle, oxidation-reduction, and stress response suggests presence of systemic regulation of fire blight infection in apples [11,38]. Moreover, rootstock genotypes can significantly contribute to scion tolerance to fire blight susceptibility via rootstock-regulated gene expression patterns [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations